2008
DOI: 10.1093/ajcn/88.4.1097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moderate alcohol consumption on liver enzymes increases with increasing body mass index

Abstract: Background: Although both ethanol consumption and overweight alter the activities of hepatic enzymes in circulation, the differentiation of an alcohol or nonalcohol basis for such changes remains problematic. The magnitude of alterations occurring among moderate drinkers has remained obscure. Objective: We examined the links between moderate ethanol consumption, body mass index (BMI; in kg/m 2 ), and liver enzymes. Design: Serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), and ␥-glutamyltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
88
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 48 publications
8
88
4
Order By: Relevance
“…Similar to Ghouri et al (13 ), we also observed a trend toward a stronger positive association between GGT and CVD mortality in the younger age group, although it should be noted that the 95% CIs were wide and included overlap between the 2 age groups (see online Supplementary Table 2). Previously, it has been shown that there is a greater effect of moderate alcohol consumption to increase liver enzymes with increasing BMI (17 ), and in men, synergism has been demonstrated between smoking and alcohol use to increase GGT levels (18 ). Interestingly, our data demonstrated a strong association between GGT and cancer mortality in nonsmokers and also showed a significant interaction between smoking status and GGT enzyme activity levels (in the association between GGT and cancer mortality).…”
Section: Discussionsupporting
confidence: 67%
“…Similar to Ghouri et al (13 ), we also observed a trend toward a stronger positive association between GGT and CVD mortality in the younger age group, although it should be noted that the 95% CIs were wide and included overlap between the 2 age groups (see online Supplementary Table 2). Previously, it has been shown that there is a greater effect of moderate alcohol consumption to increase liver enzymes with increasing BMI (17 ), and in men, synergism has been demonstrated between smoking and alcohol use to increase GGT levels (18 ). Interestingly, our data demonstrated a strong association between GGT and cancer mortality in nonsmokers and also showed a significant interaction between smoking status and GGT enzyme activity levels (in the association between GGT and cancer mortality).…”
Section: Discussionsupporting
confidence: 67%
“…Another large-scale study by Kozakova et al, in which the subjects were free of CVD, HT, DL, DM and metabolic syndrome, examined the association between the fatty liver index (FLI) (an index used to predict the presence of fatty liver) and carotid atherosclerosis. These authors reported the following conclusions: 1) FLI is a significant predictor of an increased mean carotid IMT, but not an elevated serum GGT level, when FLI is replaced by parameters used in its equation (BMI, waist circumference, serum triglyceride level and serum GGT level) and 2) FLI is a significant predictor of carotid plaque, with an elevated serum GGT level also being identified as a significant predictor when hol consumption 25) , smoking 26) , an older age 27) and obesity 28) can increase the serum GGT levels and thereby modify the relationship between fatty liver and the serum GGT level. Therefore, our analyses were conducted to clarify the manner in which fatty liver and an elevated serum GGT level are associated with carotid atherosclerosis in the same logistic regression model.…”
Section: Discussionmentioning
confidence: 98%
“…Chronic alcohol consumption or obesity due to high-fat diet causes dysbiosis and increased gut permeability to PAMPs such as LPS, which enters portal circulation and activates hepatic Macs (HMacs) in ASH or nonalcoholic fatty liver disease (16,17). We previously reported a mouse model of advanced ASH produced by a combination of high-fat diet overfeeding and alcohol intake (OF+Alc mouse) (19) -a condition often seen in obese alcoholic patients (20)(21)(22). In the present study, we used HMacs Metabolic reprogramming is implicated in macrophage activation, but the underlying mechanisms are poorly understood.…”
Section: Introductionmentioning
confidence: 99%